Mechanical and Fresh Properties of Sustainable Kenaf Fibrous Concrete Incorporating Sorghum Husk Ash - Ogunbode, Ezekiel Babatunde; Dodo, Yakubu Aminu; Moveh, Samuel (International Journal of Sustainable Construction Engineering and Technology, 2021)
This article describes the findings of an experimental investigation on the performance of concrete using Kenaf Fiber (KF) and Sorghum Husk Ash (SHA) (CEM 1). To characterised the SHA (EDS), microstructural studies such as X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray fluorescence (XRF), and Energy-dispersive X-ray spectroscopy were performed. CEM 1 was used with the KBF (length, L = 50 mm) and five volume fractions ranging from 0 to 1.0 percent ( = 0.25 percent ). Following that, five concrete mixtures were cast with 10 percent SHA as a substitute for CEM 1. The samples were cured in water and their characteristics were evaluated in both the fresh and hardened stages. In new concrete, the use of Kenaf fibre and SHA lowered slump values while increased VeBe time. When Kenaf fibre was added to either CEM 1 or SHA concrete mixes, it resulted in a good interaction with high tensile and flexural strengths, as well as increased concrete ductility and crack dispersion. When 0.5 percent Kenaf Fibre was added to dry concrete at the age of 56 days, it resulted in the largest increase in tensile and flexural strengths. The research found that utilising KF and SHA to manufacture sustainable green concrete is both technologically and environmentally viable